A Brief History of Spiral Dynamics - Albion M. Butters (Finland, 2022)
For nearly two decades, the theory of Spiral Dynamics has been used to dynamically model human evolution and information systems. In that time, however, many different versions and applications of the model have emerged. This article will diachronically trace the history of Spiral Dynamics, from the foundational theory of Clare Graves to its initial introduction by Don Beck and Chris Cowan and subsequent adaptation by Ken Wilber. A brief exploration of the various camps and their competing interpretations of Spiral Dynamics will permit some critical analysis of the model itself.